Analysis of Combustion Temperature on the Use of B100 and B20 Fuels that Operate in the Long Term - W Saputro; J Sentanuhady; L Edahwati; A K Faizin (Biomedical and Mechanical Engineering Journal (BIOMEJ), 2022)
The dependence of the Indonesian people on the use of diesel fuel is still very high and is proven by the increasing consumption of diesel annually. Increasing diesel fuel consumption is a problem that must be anticipated because diesel is a fossil of fuel and non-renewable. One way to overcome this is to convert the use of fuel from fossil fuels to biofuels, such as biodiesel fuel. Biodiesel from palm oil is an option because Indonesia is the largest palm oil-producing country globally. Although theoretically, biodiesel can be used directly in diesel engines, there are very few studies related to the effects of using biodiesel and the potential for further development. Therefore, this study aims to analyze the combustion temperature of B100 and B20 fuels operated in long-term testing. This study uses two Kubota diesel engines with a cylinder volume of 376 ccs each. Each engine will be coupled with a generator to power the halogen lamps with a total power of 4000 W. The two engines will use different fuels, the first engine will be filled with B20 fuel, and the second engine will be filled with B100 fuel from palm oil. The engine rotational speed is constant at 2200 rpm, and the engine is operated for 300 hours without stopping. Every multiple of 4 hours, the combustion temperature measurement is carried out on the cylinder head, cylinder block, and exhaust gas pipe. The results show that the B100 engine produces lower combustion temperatures in the cylinder head, cylinder block, and pipe exhaust gas with 1.7%; 1.2%; and 2.7%, respectively.